Isolation and characterization of the vitelline layer of sea urchin eggs (The Rockefeller University Press, 1977)
The vitelline layers (VLs) of unfertilized sea urchin eggs were isolated by homogenization in a hypotonic medium containing Triton X- 100 and EDTA. The surface topography of the VL is not changed by isolation. The thickness of the isolated VLs (300-400 A) is greater than that reported for VLs on intact eggs (100-200 A). Sperm adhere to the isolated VLs. When both internal and external VL surfaces are accessible to sperm, the sperm attach only to the external surface, suggesting that the external surface may carry sperm receptor proteins not present on the internal surface. Sodium dodecyl sulfate (SDS)- polyacrylamide gel electrophoresis shows that isolated VLs are composed of numerous proteins ranging from greater than 213,000 to 25,000 daltons. Lactoperoxidase-catalyzed 125I-iodination of unfertilized eggs labels two high molecular weight bands that stain faintly for carbohydrate. VLs are 90% protein and 3.5% carbohydrate. No predominance of a single amino acid or class of amino acids was found. Carbohydrate analysis yields fucose, mannose, galactose, glucose, xylose, glucosamine, galactosamine, and sialic acid. Controls for purity indicate that isolated VLs contain 2% protein of cytoplasmic origin and no more than 2.5% egg jelly.